SYNERGISTIC INTERFACIAL CHEMISTRY OF HUMIC ACID AND ACTIVATED FLY ASH FOR HIGH-PERFORMANCE Mn²⁺ ADSORPTION - Ninik Triayu Susparini; Alamsyah Sultan Ramadhan; Lusi Aferta; Marlon Jusak Renaldy Benu; Sri Wijayanti; Ali Tantowi (Fakultas Teknik Universitas Wahid Hasyim, 2026)
This study developed a hybrid adsorbent derived from activated fly ash (FA) and humic acid (HA) for effective Mn²⁺ removal from aqueous solutions. Fly ash was activated using 1 M NaOH to increase its surface hydroxyl groups (≡Si–OH and ≡Al–OH) and enhance reactivity. The activated FA was then composited with HA, which contains abundant –COOH and –OH groups, forming an inorganic–organic hybrid with improved adsorption capability. The HA–FA composite with a 1:3 mass ratio exhibited the highest Mn²⁺ removal efficiency of 98.80% after 120 minutes, significantly outperforming both HA and FA individually. FTIR analysis confirmed the formation of Si–O–C and Al–O–C linkages, indicating strong chemical interactions between the mineral and organic phases. Statistical analysis (Shapiro–Wilk, Levene, and ANOVA; p < 0.05) demonstrated that both adsorbent composition and contact time significantly influenced the adsorption efficiency. Overall, the HA–FA hybrid represents a low-cost, sustainable, and high-performance adsorbent capable of efficiently removing heavy metals from wastewater, providing a promising approach for transforming industrial and natural wastes into functional environmental materials